ARCHITECTURE OF AN INTELLIGENT NEUROCONTROL SYSTEM FOR AN AIRCRAFT WITH AN EVOLUTIONARY FORECAST OF PREFERRED BEHAVIOR - Yurich, M. Y.; Shcherbakov, A. N.; Kamyshanov, A. F. (Radio Electronics, Computer Science, Control, 2024)
In this paper are showed creation and architecture of intellectual control system (ICS) based on neural network and evolutionary algorithms for forecasting and selection of behavior for aircraft. Complex technology of the applied programming, especially in conditions of informative uncertainty, was replaced by rather simple technology of training of neural controller to react correctly to change of parameters on a control system entrance.